Community-based rural tourism: a mapping technique analysis study from 2005 to 2023 - Franklin Cordova-Buiza; Miguel Jesús Medina-Viruel; Jesús Claudio Pérez-Gálvez (Humanities & Social Sciences Communications)
Abstract Community-based rural tourism involves local communities in the management and distribution of tourism benefits, generating both social and economic impacts. However, there is a lack of systematic studies that analyse these effects in depth. This study aims to examine the evolution and trends in the scientific literature on the social and economic impacts of rural community-based tourism on the well-being of local populations between 2005 and 2023. To this end, a bibliometric analysis was carried out following the PRISMA guidelines, using VOSviewer software to map co-authorship networks, keywords and publication dynamics from data obtained from the Web of Science database. The study identified 292 scientific articles, with significant growth in the period 2017–2023. It showed that the main journals in the field were Sustainability and Journal of Sustainable Tourism, and that academic production was dominated by UK institutions. It also identified the main academic collaboration networks and the most studied concepts, highlighting the emphasis on ‘Community-based tourism’ and ‘Sustainable tourism’, and the relevance of community empowerment in tourism development. The findings reflect a growing scientific production in the last decade, but also reveal gaps in research, especially in studies that comprehensively address the effects of community-based rural tourism on the well-being of local communities. It is concluded that, while there is growing interest in the subject, more robust methodological approaches are still needed to fully understand these effects.